2016
DOI: 10.1155/2016/3982486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oil Content and Fatty Acid Profile of Ten NewCamellia oleiferaCultivars

Abstract: The oil contents and fatty acid (FA) compositions of ten new and one wild Camellia oleifera varieties were investigated. Oil contents in camellia seeds from new C. oleifera varied with cultivars from 41.92% to 53.30% and were affected by cultivation place. Average oil content (47.83%) of dry seeds from all ten new cultivars was almost the same as that of wild common C. oleifera seeds (47.06%). New C. oleifera cultivars contained similar FA compositions which included palmitic acid (C16:0, PA), palmitoleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 13 publications
(18 reference statements)
2
68
0
Order By: Relevance
“…Oil tea, an important edible oil tree species of Camellia, along with olive (Olea europaea), oil palm (Elaeis guineensis), and coconut (Cocos nucifera), are the four major woody oil species (Yang et al, 2016). Oil tea has been cultivated for more than 2300 years in southern China (Zhuang, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Oil tea, an important edible oil tree species of Camellia, along with olive (Olea europaea), oil palm (Elaeis guineensis), and coconut (Cocos nucifera), are the four major woody oil species (Yang et al, 2016). Oil tea has been cultivated for more than 2300 years in southern China (Zhuang, 2008).…”
mentioning
confidence: 99%
“…Oil tea has been cultivated for more than 2300 years in southern China (Zhuang, 2008). It is known as ''eastern olive oil'' because of its high content of unsaturated fatty acids, similar to olive oil (Dong et al, 2017;Yang et al, 2016). At present, there is an urgent need to increase the selfsufficiency of edible oil in China (Dong et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yang, Liu, Chen, Lin, and Wang () analyzed the seeds of C. oleifera containing an oil content of 41.92%–53.30% and found that the fatty acids in the seeds included palmitic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), oleic acid (C18:1), linoleic acid (C18:2), linolenic acid (C18:3), eicosenoic acid (C20:1), and tetracosenoic acid (C24:1), with the content of oleic acid being the highest one (75.78%–81.39%), followed by linoleic acid (4.85%–10.79%), palmitic acid (7.68%–10.01%), and stearic acid (1.46%–2.97%). Chaiyana et al () reported that the main fatty acids of Assam tea seed oil were oleic, linoleic and palmitic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Oil tea is a unique woody edible oil tree in China and is one of the four major woody edible oil crops in the world (Gao et al, 2015). The extracted camellia oil has several favorable characteristics, including high oleic acid content typically exceeding 80% with low saturated fats content, which are very healthy (Yang et al, 2016). Oil tea is mainly distributed in acid soil in southern China.…”
mentioning
confidence: 99%